SUBSÍDIOS TEÓRICOS E PRÁTICOS SOBRE A TEMÁTICA EVOLUÇÃO PARA FUTUROS PROFESSORES DE CIÊNCIAS - GAVRON, PAULO FERNANDO (2022)
This research results from some reflections on professional practice and teaching in Basic Education, with an emphasis on the concept of evolution, in research with a qualitative approach. In everyday use, teachers face difficulties in working on the topic, whether they are: conceptual, sociocultural and didactic strategies that contribute to understanding the key concepts of evolutionary theory. The training proposal was the preparation and application of instrumental didactics, in online format, with dynamic, attractive and relevant classes, an end-of-sequence to deepen reflections on an evolutionary theory, in a concrete context, using geological times and to the history of life on Earth as contributions to the emergence of humanity. The results obtained that the methodological practices of this initial training are completing the objective, allowing to complement and expand the teaching with an emphasis on the teaching of evolution. As a guiding principle of this initial training, Vygotsky's Socio-constructivist Learning Theory is presented as fundamental. This initial training presents a suggestive horizon of classes on the possibility of understanding evolution, considering the history of life and living beings on Earth.